PEMERIKSAAN SAKSI DALAM PERSIDANGAN TELECONFERENCE PADA MASA PANDEMI COVID – 19 - Mochamad Arief Setiawan; Otto Yudianto (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
The Covid-19 pandemic has made evidence through witness examination evidence encounter changes, which were followed by knowledge from experts in the field of science and technology. The influence of the advancement of today's science and technology into the practice of trial cases in the field of criminal procedural law that affects the proof of evidence by examining witness statements previously in the Criminal Procedure Code was required to be present in the courtroom and then examined and questioned by the judge and must also be sworn in in the room. The trial turns into witnesses who can be sworn in and asked for a statement by the judge via electronic means with the term being a teleconference trial. The practice of this teleconference trial still has to bring judges along with prosecutors and legal counsel to court, but defendants and witnesses are not welcome to come if they encounter obstacles to come and can be sworn in and asked for information via video telephone via cellphone or other electronic devices that can use the internet. The defendant and the witness still have to attend the trial directly, but it can be carried out from home or other supportive places because electronic devices are able to make judges and legal advisors and prosecutors see directly from a distance the witness and defendant through the cellphone screen. To keep up with the times, the government of the judiciary, namely the Supreme Court, issued PERMA No. 4 of 2020 concerning Administration and Trial of Criminal Cases in Courts Electronically as a regulation for holding teleconference trials. This poses a problem when viewed in the Criminal Procedure Code which requires the defendant to be present in the courtroom (Articles 154 and 196). In the criminal trial process is also based on the legal principles “Examinations are carried out directly and orally. The method used in this research is normative research method. Witness testimony delivered by teleconference is not regulated in the Criminal Procedure Code. LPSK regulates through Law 13 of 2006 article 9 emphasizing that there are 3 options for witnesses if they are not required to come in person during the trial. The Supreme Court through its regulations, namely PERMA No. 4 of 2020, explains the sequence and stages of court case affairs which are carried out by utilizing internet facilities starting from the beginning of the process to the procedure for asking witness statements via tele conference to fill legal voids that occur due to forced circumstances (Force Majeur). caused by the covid-19 pandemic